A non-classical synthetic strategy for organic mesocrystals - Wang, Shaoyan; Tran, Thu Ha; Jia, Jia; Feng, Yuhua (Frontiers in Chemistry, 2024)
Mesocrystals are ordered nanoparticle superstructures, often with internal porosity, which receive much recent research interest in catalysis, energy storage, sensors, and biomedicine area. Understanding the mechanism of synthetic routes is essential for precise control of size and structure that affect the function of mesocrystals. The classical synthetic strategy of mesocrystal was formed via self-assembly of nanoparticles with a faceted inorganic core but a denser (or thicker) shell of organic molecules. However, the potential materials and synthetic handles still need to be explored to meet new applications. In this work, we develop a non-classical synthetic strategy for organic molecules, such as tetrakis (4-hydroxyphenyl) ethylene (TPE-4OH), tetrakis (4-bromophenyl) ethylene (TPE-4Br), and benzopinacole, to produce mesocrystals with composed of microrod arrays via co-solvent-induced crystal transformation. The aligned nanorods are grown epitaxially onto organic microplates, directed by small lattice mismatch between plates and rods. Thus, the present work offers general synthetic handle for establishing well-organized organic mesocrystals.